THE INFLUENCE OF CAPITAL AND ENTREPRENEURIAL CHARACTERISTICS ON BUSINESS DEVELOPMENT AND SUSTAINABILITY: A LITERATURE REVIEW OF INDONESIAN MSMES - Gunawan Widjaja (Review of International Economy and Finance, 2026)
This study aims to review the influence of capital and entrepreneurial characteristics on business development and sustainability in MSMEs in Indonesia through a literature review approach. Capital, which includes financial, social, and intellectual capital, has been proven to be a major factor in supporting the expansion, innovation, and increased competitiveness of MSMEs. Additionally, entrepreneurial characteristics such as risk-taking, proactivity, innovation, flexibility, and managerial skills play a crucial role in the adaptation, growth, and resilience of businesses in the face of dynamic competition. This literature review confirms that the synergy between the availability of capital and the strength of entrepreneurial characteristics significantly contributes to the development and sustainability of SMEs in Indonesia. The implications of this study highlight the importance of strengthening capital capacity and entrepreneurship training, as well as an inclusive ecosystem to enhance the sustainability of the SME sector as a driving force for the national economy.